Optimization of Mould Method for Dipping Process to Produce Antimicrobial and Biodegradable Glove Containing Cassava-Peel & Soy Lecithin as Fillers - Muhammad Iman Shahfudin Karim,; Aliff Hisyam A Razak, (Progress in Engineering Application and Technology, 2023)
The COVID-19 virus has spread awareness and the demand for biodegradable composite gloves is increasing. The objective of this study is to optimize the condition in which bio-based fillers loaded gloves with good biodegradable and antimicrobial properties can be prepared using the dipping method process with the Taguchi method performed by using XLSTAT and Microsoft Excel. The cassava-peel starch was acquired by using extraction as a bio-based filler along with soy lecithin. The ratio between two fillers and mixing speed was optimized using the design of an experiment with Taguchi in which the SN Ratio with the concept “the bigger the better” has been used. From the data, it was observed after 30 days of soil burial test using SEM, the biodegradable properties of the films prepared were increasing when the cassava-peel filler increased. The mechanical testing shows excellent performance of the film’s tensile strength at 30 phr cassava peel filler, 30 phr soy lecithin filler and 450 rpm mixing speed (NRL3). By using the Taguchi method, the SN ratios show the A2B2C3 (Cassava-peel filler at 30 phr, Soy lecithin filler at 30 phr and mixing speed at 450 rpm) was the best conditions to prepare biodegradable glove using the dipping process. Other states also can be further studied in the future such as the vulcanization and pre-vulcanization temperature, maturity period for NRL and mixing time.